Fibre Optic Infrastructure for Network Deployment Using Application System - Saravanan K; V Mathivananr (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Fiber optic has an imperative part in the improvement of media communications framework in Indonesia. Better system execution and nature of the speed that offered by fiber optic can bolster the information prerequisite which keeps on expanding each year. In Indonesia, Fiber Optics is utilized as the essential system foundation Backbone and Access and still keep on developing the fiber optic system in Indonesia. Therefore, the process of reporting, controlling and monitoring are imperative for network deployment of fiber optic network by using an application system to be more efficient and accelerate the decision making process. In this study FOMApps is made, an android based application that facilitates the requirements of monitoring, controlling and reporting the fiber optic project between the Government and fiber optic deployment provider. Specifically, FOMApps incorporate distinctive announcing positions for each sort of employment. The test aftereffects of detailing framework Optical Fiber Cable (Outside Plant) has a speed in conveying the report added up to 257.516 seconds. So from the outcomes that are acquired, the application is plausible for use in detailing the arrangement of Outside Plant Fiber Optic. With the presence of this application, we expect the way toward controlling and checking between the Government and fiber optic organizations suppliers are accomplished.